KOJAK encodes a cellulose synthase-like protein required for root hair cell morphogenesis in Arabidopsis. - Favery, B; Ryan, E; Foreman, J; Linstead, P; Boudonck, K; Steer, M; Shaw, P; Dolan, L (2001)
The cell wall is an important determinant of plant cell form. Here we define a class of Arabidopsis root hair mutants with defective cell walls. Plants homozygous for kojak (kjk) mutations initiate root hairs that rupture at their tip soon after initiation. The KJK gene was isolated by positional cloning, and its identity was confirmed by the molecular complementation of the Kjk(-) phenotype and the sequence of three kjk mutant alleles. KOJAK encodes a cellulose synthase-like protein, AtCSLD3. KOJAK/AtCSLD3 is the first member of this subfamily of proteins to be shown to have a function in cell growth. Subcellular localization of the KOJAK/AtCSLD3 protein using a GFP fusion shows that KOJAK/AtCSLD3 is located on the endoplasmic reticulum, indicating that KOJAK/AtCSLD3 is required for the synthesis of a noncellulosic wall polysaccharide. Consistent with the cell specific defect in the roots of kjk mutants, KOJAK/AtCSDL3 is preferentially expressed in hair cells of the epidermis. The Kjk(-) phenotype and the pattern of KOJAK/AtCSLD3 expression suggest that this gene acts early in the process of root hair outgrowth. These results suggest that KOJAK/AtCSLD3 is involved in the biosynthesis of beta-glucan-containing polysaccharides that are required during root hair elongation.